Electronic Payment Systems in E-Business (International Journal of Food and Nutritional Sciences, 2022)
The contemporary business practises, the incorporation of this element has emerged as a fundamental and indispensable component of strategic planning, exerting a pervasive influence across all facets of the organisation. Electronic commerce, often known as e-commerce, is a multifaceted phenomenon facilitated by Information and Communication Technologies (ICTs), whereby the exchange of goods and services takes place. It has emerged as a prominent avenue for conducting commercial transactions. In the present day, characterised by significant advancements in science and technology, a new paradigm of commercial transactions has emerged, often referred to as e-commerce. This paper compares the use of previous cash systems and the new systems with the banks, payment interfaces and other modes for the better transaction management of the companies under e-Business.